1999
DOI: 10.1021/jf971043a
|View full text |Cite
|
Sign up to set email alerts
|

Further Studies on the Analysis of DSP Toxin Profiles in Galician Mussels

Abstract: Vous avez des questions? Nous pouvons vous aider. Pour communiquer directement avec un auteur, consultez la première page de la revue dans laquelle son article a été publié afin de trouver ses coordonnées. Si vous n'arrivez pas à les repérer, communiquez avec nous à PublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. Questions? Contact the NRC Publications Archive team atPublicationsArchive-ArchivesPublications@nrc-cnrc.gc.ca. If you wish to email the authors directly, please see the first page of the pub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2003
2003
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 17 publications
1
3
0
Order By: Relevance
“…A positive detection of GYM-B in clams also occurred in a previous study (Naila et al, 2012). Acyl ester metabolites have been observed for a variety of marine phycotoxins in a range of shellfish species (Comesaña Losada et al, 1999;Garcıá et al, 2004;JØrgensen et al, 2005;Torgersen et al, 2008a;2008b;Wilkins et al, 2006). Based on previous reports of acyl ester metabolites for other classes of cyclic imines including spirolides (Aasen et al, 2006) The feeding experiment demonstrated the acylation process under controlled laboratory conditions.…”
Section: Discussionsupporting
confidence: 52%
“…A positive detection of GYM-B in clams also occurred in a previous study (Naila et al, 2012). Acyl ester metabolites have been observed for a variety of marine phycotoxins in a range of shellfish species (Comesaña Losada et al, 1999;Garcıá et al, 2004;JØrgensen et al, 2005;Torgersen et al, 2008a;2008b;Wilkins et al, 2006). Based on previous reports of acyl ester metabolites for other classes of cyclic imines including spirolides (Aasen et al, 2006) The feeding experiment demonstrated the acylation process under controlled laboratory conditions.…”
Section: Discussionsupporting
confidence: 52%
“…However, the MS studies reported herein using the sodium adducts of DTXs demonstrates that it is possible to develop rapid LC multiple tandem MS methods for the determination of OA and DTX2 using unique ion transitions without the requirement of chromatographic separation. This is especially advantageous since OA and DTX2 frequently co‐occur in contaminated shellfish harvested from the western coastline of Europe …”
Section: Resultsmentioning
confidence: 99%
“…This is especially advantageous since OA and DTX2 frequently co-occur in contaminated shellfish harvested from the western coastline of Europe. [39,40]…”
Section: Dinophysistoxins: Ftms Cid Ms N Of the [M + Na] + Ionsmentioning
confidence: 99%
“…In France, it has been suggested that differences in risk of oesophageal cancer might be due to exposure to okadaic acid, a tumour promoter that is the main toxin present in French coastal waters. Regular shellfish consumers could be exposed to okadaic acid, also detected in mussels in Galicia, a site of important industrial mussel production [53,54]. It would be interesting to investigate if these marine biotoxins might be linked to the excess risk of oesophageal cancer that appears in this and other geographical areas in our country in subsequent studies.…”
Section: Discussionmentioning
confidence: 99%